Avaliação das condições de oxirredução em sistema alagado construído de escoamento horizontal subsuperficial - Gabriel Rodrigues Vasconsellos (2015)
This research aimed to evaluate the environmental conditions (redox potential, dissolved oxygen, pH, temperature and solar radiation) in two Constructed Wetland Systems (CWS), one planted with Typha latifolia and the other not planted, both with subsurface horizontal flow. The CWS served as post-treatment of the effluent from a UASB reactor, which received raw sewage. Each treatment unit has a capacity to treat approximately 50 inhabitants. Both units have been operating for about seven years with a flow rate of 7,5 m3/d. The filter bed of both units is in an advanced state of clogging. Each CWS is 25 meters long, 3 meters wide and have bed height of 0.4 meters, using blast furnace slag as a means of support. The monitoring of environmental conditions was conducted at two points along the length (inlet region and outlet region of the bed), of the planted and not planted units, and six fixed bed reactors (FBR), for evaluating the influence of vegetation and differences of environmental conditions along the length of each bed. In addition to the comparison along the length, environmental conditions were also investigated in the FBR planted with Typha latifolia, with Canna x genaralis, as well as the not planted. The results indicate a predominance of reducing conditions in the CWS. The presence of vegetation increased redox potential values and reduced pH values, keeping them close to neutral. In general, the redox potential values, dissolved oxygen concentration and pH values were higher at the outlet region of the planted CWS and not planted CWS.